A hybrid construct with tailored 3D structure for directing pre-vascularization in engineered tissues - Sara C. Neves; Aureliana Sousa; Diana S. Nascimento; Iasmim D. Orge; Sílvia A. Ferreira; Carlos Mota; Lorenzo Moroni; Cristina C. Barrias; Pedro L. Granja (Materials Today Bio)
Hybrid 3D constructs combining different structural components afford unique opportunities to engineer functional tissues. Creating functional microvascular networks within these constructs is crucial for promoting integration with host vessels and ensuring successful engraftment. Here, we present a hybrid 3D system in which poly (ethylene oxide terephthalate)/poly (butylene terephthalate) fibrous scaffolds are combined with pectin hydrogels to provide internal topography and guide the formation of microvascular beds. The sequence/method of seeding human endothelial cells (EC) and mesenchymal stromal cells (MSC) into the system had a significant impact on microvessel formation. Optimal results were obtained when EC were directly seeded onto the fibrous scaffold, followed by the addition of hydrogel-embedded MSC. This approach facilitated the development of highly oriented microvascular networks along the fibers. These networks were lumenized, supported by a basement membrane, and stabilized by pericyte-like cells, persisting for at least 28 days in vitro. Furthermore, culture under pro-angiogenic and osteoinductive conditions induced MSC osteogenic differentiation without impairing microvessel formation. Upon subcutaneous implantation in mice, the pre-vascularized constructs were infiltrated by host vessels, and human microvessels were still present after 2 weeks. Overall, the proposed hybrid 3D system, combined with an optimized cell-seeding protocol, offers an effective approach for directing the formation of robust and geometrically oriented microvessels, making it promising for tissue engineering applications.